PERANAN GURU MATA PELAJARAN DALAM MENGATASI KESULITAN BELAJAR PESERTA DIDIK YANG MEMPEROLEH HASIL BELAJAR RENDAH (Studi Deskriptif Pada Kelas VIII di SMP Negeri 2 Pancung Soal) - Sari, Novita - (Bimbingan dan Konseling, 2014)
This research was motivated by the role of subject teachers in overcoming thelearning difficulties of students who earn a low learning outcomes, which is still not effectiveas there are some students who have problems in learning for example the lack of learningmaterials and equipment owned by students, rarely in homework, lack of concentration in thestudy and could not concentrate while studying. The aimed of this study to describe the roleof subject teachers in the diagnosis of learning difficulties of students, the assistanceprovided and follow-up will be done by the subject teachers. This type of research isclassified as descriptive research with quantitative approach, namely the study population oflearners with learning difficulties characterized by the achievement of a minimumcompleteness criteria (KKM), amounting to 42 people. Sampling technique in total samplingthe number 42. Data collection tools such as questionnaires and data analysis usingtechniques hypothetical mean. The results of this study revealed that the role of the teacher inthe school subjects: 1) diagnosis of learning difficulties participants had either 2) To provideassistance to students who have difficulty learning felt good and 3) follow-up is conducted bysubject teachers to participants students who have difficulty learning felt good.